Entre coturnos e cartilhas: um estudo sobre o Programa de Implantação das Escolas Cívico-Militares no Brasil – PECIM - Leite, Dorgival Renê Tolentino (2023)
The political context in which we live, notably after the removal of President Dilma Vana Rousseff from power in 2016, until the end of the Government of President Jair Messias Bolsonaro, led to a series of structural changes in the various areas of the Brazilian government, which awakened considerable concern due to the visible deconstitution of rights and the formulation of a true nation project linked to the interests of the Brazilian armed forces and elitists. Education, in turn, was one of the most affected departments, so that several plans and programs, among other public policies, were extinguished to make way for a series of measures that deserve urgent scientific studies. From this perspective, among the new measures adopted, the Civic- Military Schools Implementation Program – PECIM was established, the characteristics and aspects of which remain obscure from a scientific point of view, as there are still few academic works on the subject. Indeed, considering the need for more in-depth research on the subject, the present work aimed to investigate how PECIM was created amid the government proposals of then President Bolsonaro (2019 – 2022), so that we can understand the historical, cultural conceptions and social, always with the interest of understanding their real ideological and pedagogical foundations. The research, in turn, is exploratory, so we will appropriate historical and dialectical materialism, whose sources of exploration are documentary and bibliographic. We aim to expand studies on the subject, in order to work with the classics of dialectical historical materialism, as they are capable of providing theoretical and methodological foundations that make it possible to achieve the objective proposed in this study. In the end, the result of the study presented a discussion about the implementation of civic-military schools, bringing to light their ideological, social, cultural and political perspectives, which led to the observation of a change in paradigms related to education through a fallacious program and against the achievements and struggles for minority rights, such as combating social inequality, homophobia, racism, prejudice, poverty, exploitation, violence against children and adolescentes.